Pola Asuh Orang Tua Terhadap Kedisiplinan Dalam Mengikuti Pembelajaran Daring Selama Masa Pandemi Covid 19 - Maryanti (INVOLUSI: Jurnal Ilmu Kebidanan, 2022)
During the COVID-19 pandemic, the government imposed rules for online learning, this change in the learning system of course must also be followed by changes in parenting patterns for their children at home. Various forms of parenting will certainly have implications for the formation of children's character. Parents who are actually the closest environment for children, all of their behavior will be observed and even imitated by the child himself. During this pandemic, parents experience changes in parenting patterns, because initially they are school children, while now children are full at home, so parents also adjust their roles. This research is quantitative, with a cross-sectional design approach. Population : Parents who have school children, Sample : parents who have school children , Sampling technique : incidental sampling (anyone who is willing to fill out the questionnaire, when the questionnaire is shared through social media), Hypothesis testing using correlation test, with Simple Pearson Test ( value of r). Research results: it is known that of the 26 respondents who filled out the questionnaire, there were 80.7% applying democratic parenting, and 11.5% applying authoritarian parenting and 7% applying permissive parenting. It is known that 34.6% of respondents stated that their children were disciplined in participating in online learning, while 65.3% stated that their children lacked discipline in participating in online learning during this covid-19 pandemic. Analysis of the data with a simple Pearson Correlation test obtained the results of the value of r = -0.03227. This means that the value of the correlation coefficient is close to 0 (zero) which means that the data pair of the variable parenting in children and the variable of discipline in participating in online learning has a very weak correlation